Causas da distribuição de aves da Amazônia: uma questão da escala taxonômica - Essig, Isadora Fluck (2020)
One of the main questions in biogeography is the role of cladogenesis across barriers vs. ecological specialization on species distribution. In Amazonia, rivers have long been hypothesized to limit species dispersal and promote cladogenesis, affecting species distribution. However, recent ecological studies suggest that species distribution is more affected by environmental conditions (e.g. climate) than by rivers, which could indicate that ecological specialization is more important to community assembly. Because evolutionary and ecological studies often use distinct data (e.g. small vs. large groups of species) and statistical approaches, the relative role of environmental conditions and rivers on species cladogenesis and distribution is not well established. We created a comprehensive database of bird occurrences (39,732 records) to determine the importance of environmental conditions (ecological factors) and cladogenesis across rivers (evolutionary factor) for the distribution of endemic species in Amazonia. We then compare the distribution of endemic clades vs. all birds to determine if results obtained from endemic clades can be extrapolated to broader taxonomic scales (i.e. whole communities including all clades). Rivers were the most important factor affecting the cladogenesis and distribution of endemic clades. However, the distribution of the whole bird community in Amazonia was more strongly associated with temperature than to rivers. These results indicate that environmental gradients and barriers importance to species distribution depends on the taxonomic scale. Therefore, results obtained from an entire class, order or other broad clade should not be compared to results obtained from genera or other less inclusive clades.